Rare Presentation of Hypoglycemia in a Patient with Anaplastic Large-Cell Lymphoma - Raed Aldahash (Case Reports in Endocrinology)
Anaplastic large-cell lymphoma is a rare type of aggressive non-Hodgkin’s lymphoma, and arriving at a final diagnosis for this tumor is a challenge for the healthcare providers. Usually, it involves the lymph nodes and extranodal tissues such as the lungs, skin, and other soft tissues. Its presentation by extending into different organs such as the liver, lungs, bones, spleen, and thyroid is rare. Thus, involvement of other organs is very rare as we found in a 54-year-old male patient, a known case of hypertension and end-stage renal disease who was on hemodialysis, who presented to the emergency department with a history of generalized weakness and weight loss of about 20 kg for two months. The tumor cells are positive for CD45, CD30, CD15, MUMi, and Ki-67 (80%) and negative for CD20, PAX-5, CD79a, CD3, CD5, CD10, BCL6, BCL2, EMA, ALK-1, and CD138. The patient was hypoglycemic and hypercalcemic and was managed accordingly. The patient was evaluated, and the third assessment showed that hypoglycemia was resolved due to dexamethasone. The patient’s glucose storage was depleted most likely due to liver involvement plus poor general condition. It was asserted that the patient’s hypoglycemia could be related to his underlying malignancy. Also, the patient was advised to start tablet diazoxide 45 mg three times a day (3 mg/kg/day TID) in addition to levothyroxine tablet 50 mcg once a day. Tablet diazoxide was stopped, and nutritional support was recommended. This case reveals a rare systematic ALK-1-negative anaplastic large-cell lymphoma that involves multiple organs. The main learning point from this report is that these tumors can present atypically even in adults and can be ALK-1 negative, which is contrary to the typical systematic anaplastic large-cell lymphomas that are positive for ALK.